Dynamic cake / Muhammad Imran Rahmat ... [et al.] - Rahmat, Muhammad Imran; Abu Bakar, Nuratikah; Baharudin, Mohd Norsazli; Rosman, Muhammad Hafif; Salim, Kamil Sidqi; Edy, Azizah (2017)
Our company's name is Dynamic Cake. Our business provide the set of lemon cake with pavlova for dessert based on good quality of material. We combine both of this to make it more tasty and easy to eat. For our business, we are provide set of dessert which is lemon cake with pavlova as our major product because we know the product is marketable in local and international market since it is a food that everyone in this world eat and we try to make something unique. Our business center is located in No 56, Jalan Rivera 1, Maharani Rivera, 84000 Muar/Tangkak, Johor. We have registered-our company on 2nd November 2017. Our business will start operate on 8 January 2018. There are a few reason why we choose this particular business it is because it help eat in easy way by combining both lemon cake and pavlova. It's also give a taste of sweet (pavlova) and sour (lemon cake) that can make our customer satisfied with our product. The future prospective of the business: - Hope that this company will continue to evolve with the ever-increasing profit. - Keep on update our product base on customer demand. - Keep on making a new product. - Survive in the sourcing the product. - Increase the number of customer continuously. - Improve our management system in business. - Enlarge our scope in business.